Metabolomics-based investigation of SARS-CoV-2 vaccination (Sinovac) reveals an immune-dependent metabolite biomarker - He, Maozhang; Huang, Yixuan; Wang, Yun; Liu, Jiling; Han, Maozhen; Xiao, Yixuan; Zhang, Na; Gui, Hongya; Qiu, Huan; Cao, Liqing; Jia, Weihua; Huang, Shenghai (Frontiers in Immunology, 2022)
SARS-CoV-2 and its mutant strains continue to rapid spread with high infection and fatality. Large-scale SARS-CoV-2 vaccination provides an important guarantee for effective resistance to existing or mutated SARS-CoV-2 virus infection. However, whether the host metabolite levels respond to SARS-CoV-2 vaccine influence host immunity remains unclear. To help delineate the serum metabolome profile of SARS-CoV-2 vaccinated volunteers and determine the metabolites tightly respond to host immune antibodies and cytokines. In this study, a total of 59 sera samples were collected from 30 individuals before SARS-CoV-2 vaccination and 29 COVID-19 vaccinees 2 weeks after the two-doses of vaccination. Next, untargeted metabolomics was performed and a distinct metabolic composition was revealed between pre-vaccination (VB) group and 2-doses of vaccination (SV) group by partial least squares-discriminant and principal component analyses. Based on the criteria: FDR < 0.05, absolute log2 fold change greater than 0.25 and VIP >1, we found L-Glutamic acid, gamma-Aminobutyric acid (GABA), Succinic acid and Taurine showed increasing trends from SV to VB. Furthermore, SV-associated metabolites were mainly annotated to Butanoate Metabolism and Glutamate Metabolism pathways. Moreover, 2 metabolite biomarkers classified SV from VB individuals with an area under the curve (AUC) of 0.96. Correlation analysis identified a positive association between 4 metabolites enriched in Glutamate Metabolism and serum antibodies in related to IgG, IgM and IgA. These results suggest that the contents of gamma- Aminobutyric acid and Indole in serum could be applied as biomarkers in distinguishing vaccinated volunteers from unvaccinated. What’s more, metabolites such as GABA and Taurine may serve as a metabolic target for adjuvant vaccines to boost the ability of the individuals to improve immunity.